Sociopolitical Dynamics In Relations Between Top Managers and Security Analysts: Favor Rendering, Reciprocity, and Analyst Stock Recommendations - Westphal, James D.; Clement, Michael B. (Academy of Management Journal, 2008)
We examine how the disclosure of negative firm information may prompt top executives to render personal and professional favors for security analysts, who may reciprocate by rating firms relatively positively. We further examine how negative ratings may prompt executive negative reciprocity toward an analyst and how such retaliation may deter other analysts' negative ratings. Because analyst recommendations influence investor behavior, firm reputation, and access to capital, our theory and supportive findings suggest that corporate leaders enhance and perpetuate external support for their firms via social influence processes that develop and maintain social exchange relations with a key type of external constituent.